Conduction system pacing with Selectra 3D Sheath: Technical Results. (19th May 2022) - Marcantoni, L; Centioni, M; Pastore, G; Baracca, E; Marsiglia, S; Fornasaro, M; Pigaiani, C; Cappato, E; Manzato, E; Zanon, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Conduction system pacing (CSP) allows physiological electrical activation. The Selectra3D sheath is a new tool able to guide the lead implantation on the His Bundle (HBP) or on the left bundle branch (LBBP). It does exist in 3 different shapes (40-S, 55-M, 65-L). Objective: To evaluate the effectiveness of different Selectra3D introducers for CSP, considering the procedural success, stability of electrical parameters or need for implant revision at medium-term follow-up. Methods and results: Selectra3D was used in 113 CSP procedures between Nov 2019 and Nov 2021. Mean patients age was 80±6 years, 54% males. Pacing indications were: AV block 52.2%, slow AF 12.4%; SND 12.4%, ablate&pace 5.3%, implant revision 0.9%, cardiomyopathy 16.8%. Mean EF was 40±15%. Single chamber PM was implanted in 4.8% pts, dual chamber PM in 57.1% pts while 26.2% and 11.9% pts received CRT-P and CRT-D devices respectively. Stylet-driven lead was used in 75 pts, fixed screw lead in 38 pts. HBP was obtained in 34% pts, LBBP in 55% pts, HBP+LBBP in 3% pts, while 8% cases were CSP implant failure (7 lead implanted in the septum; 2 in the coronary sinus). Selectra3D was the first delivery used during the procedure in 88% of cases (55-M in 76%; 40-S in 9%; 65-L in 3%), while was the second tool (after failure of the first delivery utilised) in the other pts. The first Selectra3D utilized during each implant was able to complete the procedure in 64% of cases, while in the other pts a second different tool was required to complete the implant. The Selectra3D 55-M was the mostly used and was able to reach the final position in most cases. In dilated atria the 65-L curve was preferred, while when the target point was more proximal the 45-S curve was the best choice. The baseline QRS duration was 135 ± 34 ms and the paced QRS duration was 113 ± 18 ms (P 0.003). The electrical parameters were optimal with sensing 8.7 ± 8 mV; impedance 562 ± 133 ohm; threshold 0.97 ± 0.47 V. During a median follow-up of 178 [34-402] days, 7 lead dislodgement (3 HBP and 4 LBBP) were recorded. All the others showed stability of the electrical parameters. Conclusion: The Selectra3D introducers effectively supports CSP ensuring procedural success rate>90%. The 55-M curve fits for most of the anatomies, the 45-S curve allows to reach more proximal target, the 65-L curve more distal target in dilated atria. The electrical parameters were optimal at implant and remained stable during follow-up. 6% lead dislodgement were recorded.